2007
DOI: 10.1007/s00109-007-0219-9
|View full text |Cite
|
Sign up to set email alerts
|

Alternative splicing of the FGF antisense gene: differential subcellular localization in human tissues and esophageal adenocarcinoma

Abstract: Overexpression of FGF-2 is associated with tumor recurrence and reduced survival after surgical resection of esophageal cancer, and these risks are reduced in tumors co-expressing the FGF antisense (FGF-AS) RNA. The aim of this study was to characterize the expression of alternatively spliced FGF-AS transcripts and encoded nudix-motif proteins in normal human tissues and in esophageal adenocarcinoma, and to correlate their expression with clinicopathologic findings and outcome. Three alternatively spliced FGF-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
25
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(28 citation statements)
references
References 48 publications
3
25
0
Order By: Relevance
“…This natural antisense of the Fgf2 gene is induced in many pathological conditions. 16 In the retina of the Nxnl1À/À mice at 3 months of age, the 22 and 22.5-kDa isoforms of FGF2 are more abundant in the total cell extract and the 18-kDa isoform of FGF2 is present at higher levels both in the total extract and in the nuclear fraction ( Figure 4a). By 12 months, the level of FGF2 is reduced (Figure 4b).…”
Section: Resultsmentioning
confidence: 98%
“…This natural antisense of the Fgf2 gene is induced in many pathological conditions. 16 In the retina of the Nxnl1À/À mice at 3 months of age, the 22 and 22.5-kDa isoforms of FGF2 are more abundant in the total cell extract and the 18-kDa isoform of FGF2 is present at higher levels both in the total extract and in the nuclear fraction ( Figure 4a). By 12 months, the level of FGF2 is reduced (Figure 4b).…”
Section: Resultsmentioning
confidence: 98%
“…A central regulatory factor in the gene network identified is the Nudt6 antisense transcript for the fibroblast growth factor 2 gene ( Fgf2 ) expression product. The Nudt6 is an embedded reverse transcript within the Fgf2 gene [53], [54] that has the capacity to inhibit the expression and action of FGF2 [55], [56]. This FGF2/NUDT6 relationship indicates a critical regulatory role in the gene network identified, Figure 6, to influence signal transduction processes and transcriptional regulation.…”
Section: Discussionmentioning
confidence: 96%
“…1A, right panel. Since we have recently reported that a major green tea catechin EGCG suppresses bFGF at the post translational level [7] and that the NUDT6 gene is an antisense of bFGF mRNA [11], we decided to further investigate NUDT6 in this study. NUDT6 belongs to the family of Nudix hydrolases but its function is not well known.…”
Section: Resultsmentioning
confidence: 99%
“…We previously reported that NAG-1 and ATF3 are induced by green tea catechins, and NR4A1 , ID1 , ID2 are known to play a role in tumorigenesis [2931]. In contrast, the biological function of NUDT6 and its role in tumorigenesis have not been well elucidated [11]. To elucidate the biological function of NUDT6 in human colorectal cancer cells, we generated stable cell lines with V5/His tags.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation